MoS2-Catalyzed Aerobic Synthesis of Tetraethylthiuram Disulfide in Batch and Continuous Flow - Zhao, Ze-Run; Xu, Hao-Xing; Wang, Xiao (Synlett, 2023)
Tetraethylthiuram disulfide (TETD) is one of the most important thiuram-class rubber vulcanization accelerators and a ‘star molecule’ in other areas. The development of a mild, efficient, low-cost, safe, and sustainable approach to produce TETD is extremely desirable. Here, we developed a much-improved route to synthesize TETD using MoS2 as the catalyst and ethanol as the solvent. A packed-bed microflow strategy was implemented to accelerate the catalytic process. TETD was obtained with an excellent yield and purity within a short residence time. Besides, this continuous process did not generate any waste salts, rendering it a sustainable method for producing thiuram-type compounds.
Keywords: tetraethylthiuram disulfide; molybdenum disulfide; packed-bed microflow reactor; green solvent; aerobic oxidation; sustainability